Comparative Analysis of C-Reactive Protein and Procalcitonin Levels in the Severity of COVID-19 Patients - Tuti Alawiyah; Asvin Nurulita; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Coronavirus Disease 2019 (COVID-19) is a systemic disease characterized by mild to critical symptoms with a high risk of mortality. Fast and precise inflammatory markers are needed to predict the severity and prognosis of COVID-19 to decrease the mortality rate. The elevated levels of C-Reactive Protein (CRP) and procalcitonin may predict an increased risk of aggravation in COVID-19 patients.  This study aimed to analyze the CRP and procalcitonin levels of COVID-19 severity. This was a cross-sectional retrospective study involving 160 COVID-19 patients at Dr. Wahidin Sudirohusodo Hospital. Subjects were grouped based on the severity of COVID-19 (mild, moderate, severe, critical). The difference in CRP and procalcitonin levels based on the severity of COVID-19 was analyzed using the Kruskal-Wallis test and the Spearman correlation test. The age of participants in this study ranged from 19-87 years old. The higher CRP and procalcitonin level shows heavier the severity of COVID-19 (p<0.001). This indicated a significant difference between CRP, procalcitonin levels, and the severity of COVID-19. This study showed that there was a significant correlation between CRP and procalcitonin with the severity of COVID-19, CRP (p<0.001) and procalcitonin (p<0.001).